Pengaruh Dukungan Organisasi dan Lingkungan Kerja Terhadap Adaptasi pada Kecamatan Tembalang Kota Semarang - Budy Safitri, Nur Aini (Universitas 17 Agustus 1945 Semarang, 2025)
This study aims to analyze the influence of organizational support and work environment on employee adaptation at the Tembalang District Office, Semarang City. Employee adaptation is a crucial factor in achieving work effectiveness in the government sector, especially in facing organizational dynamics and policy changes. The research sample consisted of 93 district employees selected using a census method. Data was collected through a questionnaire using a Likert scale (1–5) and analyzed using multiple linear regression in SPSS version 25. The results show that organizational support has a positive and significant effect on employee adaptation. Similarly, a conducive work environment significantly influences the improvement of employees’ adaptability. The implication of this study indicates that government organizations need to enhance support for employees and create a better work environment to foster optimal employee adaptation and performance